Techno-economic assessment of carbonate melt flue gas desulfurization process. (March 2021) - Lee, Juwon; Cho, Hyungtae; Moon, Il; Lubomirsky, Igor; Kaplan, Valery; Kim, Junghwan; Ahn, Yuchan
Abstract: Sulfur dioxide (SO2 ) is a pollutant that is mainly emitted in thermal coal-fired power plants, and it causes air pollution, which is required to be removed since it adversely affects the atmosphere environment. This study presents a novel approach to remove SO2 using carbonate melt by designing a flue gas desulfurization (FGD) process that uses a carbonate melt desulfurization (CMD) subsystem to remove >99.9 wt% of SO2 and a carbonate melt regeneration (CMR) subsystem that recovers ~99 wt% of the melt. To reduce the operating costs of the proposed process, a heat-exchanger network was developed to use the waste heat that existed in the process. The levelized cost of the proposed FGD process using carbonate melt was determined as US$ 761/ton SO2 removed and is therefore cost-competitive with other SO2 removal technologies. Sensitivity analysis indicates that coal price is the main driver of levelized cost.